Men become civilized - Cairns, Trevor (London, Cambridge U.P., 1969)
Traces the development of civilization from the first appearance of man-like creatures to the death of Alexander the Great.
Keywords: Civilization, Ancient -- Juvenile literature; Civilization, Ancient